1999
DOI: 10.1073/pnas.96.8.4402
|View full text |Cite
|
Sign up to set email alerts
|

Two heads of myosin are better than one for generating force and motion

Abstract: Several classes of the myosin superfamily are distinguished by their ''double-headed'' structure, where each head is a molecular motor capable of hydrolyzing ATP and interacting with actin to generate force and motion. The functional significance of this dimeric structure, however, has eluded investigators since its discovery in the late 1960s. Using an optical-trap transducer, we have measured the unitary displacement and force produced by double-headed and single-headed smooth-and skeletal-muscle myosins. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
112
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 38 publications
23
112
3
Order By: Relevance
“…Using optical tweezers, Tyska et al (50) showed that in case of smooth and skeletal myosins the dwell times of the singleand double-headed molecules were very similar to each other in both unloaded and loaded conditions, which is consistent with our findings for NMIIB HMM. These authors also demonstrated that the stroke sizes of the double-headed molecule smooth and skeletal muscle myosins were approximately double that of the single-headed fragment.…”
Section: Attachment Modesupporting
confidence: 91%
“…Using optical tweezers, Tyska et al (50) showed that in case of smooth and skeletal myosins the dwell times of the singleand double-headed molecules were very similar to each other in both unloaded and loaded conditions, which is consistent with our findings for NMIIB HMM. These authors also demonstrated that the stroke sizes of the double-headed molecule smooth and skeletal muscle myosins were approximately double that of the single-headed fragment.…”
Section: Attachment Modesupporting
confidence: 91%
“…9). This suggestion is supported by laser trap studies on single-headed and heterodimeric molecules which indicated that one head performs all of the work on the actin filament (24,37,38). Single-headed binding is also consistent with the very low duty cycle which myosin II exhibits under unloaded conditions (4% for both smooth and skeletal in the motility assay) (39).…”
Section: Structural Model For Regulation Of Smooth Muscle Myosin Actimentioning
confidence: 80%
“…Ultimately, cell shape changes and cell motility require, in addition to local volume changes (10), the spatial coordination of two ATP-dependent events (11)(12)(13): F-actin polymerization and motor protein-driven actomyosin contraction. Activated Rho subfamily Rho GTPases act via Rho kinases (ROCK1 and ROCK2; Rho-associated coiled-coil-containing protein kinases) to induce phosphorylation of myosin II regulatory light chains, which promotes actomyosin contraction.…”
mentioning
confidence: 99%